2017
DOI: 10.1007/s10562-017-2208-0
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Pd-nanoparticle@MIL-101(Cr) Catalysts for Tandem Reductive Amination

Abstract: The versatility of MOFs as highly porous Lewis acidic supports for precious metal nanoparticles has been exploited for one-pot tandem reductive amination catalysis. MIL-101(Cr) loaded with Pd nanoparticles ca. 3 nm in size at 0.2–1 wt% has been used to catalyse the reaction of 4′-fluoroacetophenone with benzylamine under 10 bar of H 2 to give the secondary amine, 4′-fluoro-α-methyl- N -phenylmethylbenzenemethanamine. For the highest Pd loading, major hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 20 publications
(22 reference statements)
0
39
0
Order By: Relevance
“…There is no hydrogenolysis of the benzyl group or, in 1d, of the C-Br, which would be expected using typical heterogeneous hydrogenation catalysts. [16] While the SulP1-MOF-808(Hf)-Ir gave good results in reductive amination of ketones, it is well known that reduction of aldimines is significantly easier than that of ketimines and we found that SulP1-MOF-808(Hf)-Rh was able to reductively aminate benzaldehyde (Scheme 3). With this precedent, we aimed to establish the versatile nature of SulP1-MOF-808(Hf) as an insoluble "porous phosphine ligand" with Lewis acidity, whose catalytic properties can be modified by the choice of metal precursor added.…”
Section: Resultsmentioning
confidence: 74%
“…There is no hydrogenolysis of the benzyl group or, in 1d, of the C-Br, which would be expected using typical heterogeneous hydrogenation catalysts. [16] While the SulP1-MOF-808(Hf)-Ir gave good results in reductive amination of ketones, it is well known that reduction of aldimines is significantly easier than that of ketimines and we found that SulP1-MOF-808(Hf)-Rh was able to reductively aminate benzaldehyde (Scheme 3). With this precedent, we aimed to establish the versatile nature of SulP1-MOF-808(Hf) as an insoluble "porous phosphine ligand" with Lewis acidity, whose catalytic properties can be modified by the choice of metal precursor added.…”
Section: Resultsmentioning
confidence: 74%
“…High conversions and selectivities were observed. There is no hydrogenolysis of the benzyl group or, in 1 d , of the C−Br moiety, which would be expected using typical heterogeneous hydrogenation catalysts …”
Section: Resultsmentioning
confidence: 92%
“…There is no hydrogenolysis of the benzylg roup or,i n1d,o ft he CÀBr moiety,w hich would be expected using typicalh eterogeneous hydrogenation catalysts. [16] Table 2. Optimisation of reductive amination.…”
Section: Resultsmentioning
confidence: 99%
“…Typically the literature on amination provides only the yields of the desired product at the end of the reaction without reporting kinetics. [1,2,23,28,29,46,47,51,52,56,[59][60][61] In some studies, the reaction conditions for transformations of aldehyde and ketones with amines or secondary amines were different. [11,15,17,23,49,54,61,62] Figure 2.…”
Section: Introductionmentioning
confidence: 99%